2019
DOI: 10.1093/ehjci/jez272
|View full text |Cite
|
Sign up to set email alerts
|

Potential usefulness and clinical relevance of a novel left atrial filling index to estimate left ventricular filling pressures in patients with preserved left ventricular ejection fraction

Abstract: Aims The aim of this study was to examine the potential usefulness and clinical relevance of a novel left atrial (LA) filling index using 2D speckle-tracking transthoracic echocardiography to estimate left ventricular (LV) filling pressures in patients with preserved LV ejection fraction (LVEF). Methods and results The LA filling index was calculated as the ratio of the mitral early-diastolic inflow peak velocity (E) over LA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 20 publications
1
15
0
3
Order By: Relevance
“…Peak torque of the left leg in patients with HFpEF was inversely associated with E/LAS. The elevated novel LA filling index (E/LAS ratio) was recently shown to be an effective and useful parameter to determine the elevated LV filling pressure in patients with HFpEF 26 . Accordingly, our findings show that HFpEF patients with elevated LV filling pressure (elevated E/LAS ratio) correlated with reduced muscle strength of legs.…”
Section: Discussionsupporting
confidence: 60%
“…Peak torque of the left leg in patients with HFpEF was inversely associated with E/LAS. The elevated novel LA filling index (E/LAS ratio) was recently shown to be an effective and useful parameter to determine the elevated LV filling pressure in patients with HFpEF 26 . Accordingly, our findings show that HFpEF patients with elevated LV filling pressure (elevated E/LAS ratio) correlated with reduced muscle strength of legs.…”
Section: Discussionsupporting
confidence: 60%
“…Recently, several studies have shown that left atrial strain is impaired in patients with left ventricular diastolic dysfunction, 10 and left atrial strain is well correlated with LVFP or PCWP.6 – 9 Thus, the LA filling index, the ratio of the mitral E velocity over LASr, could reflect the LA functional changes (LASr) and current LV filling status (mitral E velocity). 20 LA stiffness index comprised of the best LA strain parameter and a preferable estimated LVFP parameter (E/e′) would reveal the LA compliance influenced by LV diastolic function and the LV function affected by LVFP. 21 LAVI/LASr combines LA structure (LAVI) and LA function parameters (LASr) which influenced by LV diastolic function.…”
Section: Discussionmentioning
confidence: 99%
“…Braunauer et al. study showed that LA filling index (AUC .82) had a good diagnostic performance to determine elevated LVFP, 20 and Lin et al. study found that LA stiffness index (AUC .83) was the most accurate parameter in identifying elevated LVEDP patients from those with coronary disease.…”
Section: Discussionmentioning
confidence: 99%
“…To a certain extent, this is consistent with the results of some recent studies. Braunauer et al found that an elevated E/LASr ratio was significantly associated with worse functional capacity and HF hospitalization at 2 years [17]. A study of patients with atrial fibrillation found that an elevated E/LA strain ratio was associated with HF hospitalizations or worse cardiovascular events [18].…”
Section: Discussionmentioning
confidence: 99%